Sectoral Employment Variability and Unexpected Inflation - Ratti, Ronald A. (The Review of Economics and Statistics, 1985)
This paper considers the relationship between the variability of sectoral employment and unexpected inflation. The framework used is a multisector version of Friedman's well-known model of the business cycle. The model suggests that sectoral employment variability is a quadratic function of unexpected inflation and the rate of growth in real GNP. The model is tested using annual U.S. data on sectoral employment in the nonagricultural economy from 1901 to 1978. Inflationary surprises and the rate of real growth are found to explain between 60% and 85% of the variability in relative sectoral employment performance.